Autoantibodies against voltage‐gated potassium channel and glutamic acid decarboxylase in psychosis: A systematic review, meta‐analysis, and case series. Issue 10 (20th July 2017) - Grain, Rosemary; Lally, John; Stubbs, Brendon; Malik, Steffi; LeMince, Anne; Nicholson, Timothy R.; Murray, Robin M.; Gaughran, Fiona
Abstract : Antibodies to the voltage‐gated potassium channel (VGKC) complex and glutamic acid decarboxylase (GAD) have been reported in some cases of psychosis. We conducted the first systematic review and meta‐analysis to investigate their prevalence in people with psychosis and report a case series of VGKC‐complex antibodies in refractory psychosis. Only five studies presenting prevalence rates of VGKC seropositivity in psychosis were identified, in addition to our case series, with an overall prevalence of 1.5% (25/1720) compared to 0.7% in healthy controls (12/1753). Meta‐analysis established that the pooled prevalence of GAD65 autoantibodies was 5.8% (95% confidence interval [CI]: 2.0–15.6%; I 2 = 91%; nine studies) in psychotic disorders, with a prevalence of 4.6% (95%CI: 1.2–15.9%; nine studies; I 2 = 89%) and 6.2% (95%CI: 1.2–27.0%; two studies; I 2 = 69%) in schizophrenia and bipolar disorder, respectively. People with psychosis were more likely to have GAD65 antibodies than controls (odds ratio [OR], 2.24; 95%CI: 1.28–3.92%; P = 0.005; eight studies; I 2 = 0%). Among 21 participants with treatment‐resistant psychosis, none had VGKC antibodies. The prevalence of VGKC antibodies is low in psychosis. Our preliminary meta‐analysis suggests that GAD autoantibodies are more common in people with psychosis than in controls, although few studies accounted for the possibility of co‐existing type 1 diabetes mellitus and the clinical significance of reported GAD titers remains unclear. The paucity of studies reporting thresholds for defining GAD abnormality and rates of comorbid type 1 diabetes mellitus precludes interpretations regarding the influence of GAD antibodies on the development of psychotic disorders and may have led to an overestimate of the prevalence of GAD. Our case series fails to support the hypothesis that VGKC antibodies are linked to treatment resistance in psychosis, but the literature to date is remarkably sparse.